Distribution of segmental foot kinematics in patients with degenerative joint disease of the ankle. Issue 6 (15th December 2017) - Canseco, Karl; Kruger, Karen M.; Fritz, Jessica M.; Konop, Katherine A.; Tarima, Sergey; Marks, Richard M.; Harris, Gerald F.
ABSTRACT: Degenerative joint disease (DJD) of the ankle is a debilitating chronic disease associated with severe pain and dysfunction resulting in antalgic gait alteration. Little information is available about segmental foot and ankle motion distribution during gait in ankle osteoarthritis. The aim of the current study was to dynamically characterize segmental foot and ankle kinematics of patients with severe ankle arthrosis requiring total ankle replacement. This was a prospective study involving 36 (19 M, 17 F) adult patients with a clinical diagnosis of ankle arthrosis ("DJD" group) and 36 (23 M, 13 F) healthy subjects ("Control" group). Motion data were collected at 120 Hz using a 3‐D motion camera system at self‐selected speed along a 6‐m walkway and processed using the Milwaukee Foot Model (MFM). The SF‐36 Health Survey and Orthopaedic Foot and Ankle Society (AOFAS) ankle‐hindfoot scale were administered to evaluate functional levels. Findings include decreases in walking speed, cadence, stride length and swing phase, and reduced outcomes scores (SF‐36 and AOFAS). Multisegemental motion in patients with ankle DJD demonstrates significant changes in foot mechanics characterized by altered segment kinematics and significant reduction in dynamic ROM at the tibia, hindfoot, forefoot, and hallux when compared to controls. The results demonstrate decreased temporal‐spatial parameters and low outcomes scores indicative of functional limitations. Statement of clinical significance: Altered segment kinematics and reduced overall range of motion demonstrate how a single joint pathology affects kinematic distribution in the other segments of the foot and ankle and alters patients' overall gait. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:1739–1746, 2018.